Miniemulsion copolymerization of (meth)acrylates in the presence of functionalized multiwalled carbon nanotubes for reinforced coating applications - Pérez-Martínez, Bertha T.; Farías-Cepeda, Lorena; Ovando-Medina, Víctor M.; Asua, José M.; Rosales-Marines, Lucero; Tomovska, Radmila (Beilstein Journal of Nanotechnology, 2017)
Film forming, stable hybrid latexes made of methyl metacrylate (MMA), butyl acrylate (BA) and 2-hydroxyethyl methacrylate (HEMA) copolymer reinforced with modified multiwalled carbon nanotubes (MWCNTs) were synthesized by in situ miniemulsion polymerization. The MWCNTs were pretreated by an air sonication process and stabilized by polyvinylpyrrolidone. The presence of the MWCNTs had no significant effect on the polymerization kinetics, but strongly affected the polymer characteristics (Tg and insoluble polymer fraction). The performance of the in situ composites was compared with that of the neat polymer dispersion as well as with those of the polymer/MWCNT physical blends. The in situ composites showed the presence of an additional phase likely due to the strong interaction between the polymer and MWNCTs (including grafting) that reduced the mobility of the polymer chains. As a result, a substantial increase of both the storage and the loss moduli was achieved. At 60 °C, which is above the main transition region of the polymer, the in situ composites maintained the reinforcement, whereas the blends behaved as a liquid-like material. This suggests the formation of a 3D network, in good agreement with the high content of insoluble polymer in the in situ composites.
Keywords: electrical conductivity; hybrid polymers; mechanical properties; miniemulsion polymerization; multiwalled carbon nanotubes